2019
DOI: 10.1093/eurpub/ckz043
|View full text |Cite
|
Sign up to set email alerts
|

Does the Flemish colorectal cancer screening programme reach equity in FIT uptake?

Abstract: Background To investigate colorectal cancer (CRC) screening rates by the faecal immunochemical test (FIT) according to sociodemographic characteristics and nationality. Methods Men and women, aged 56–74, invited to participate in the Flemish CRC screening programme in 2013 and 2014 were included in this study. We analysed the association between CRC screening uptake and sex, age, (first and current) nationality and several pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 33 publications
8
17
0
Order By: Relevance
“…Our study found a lower organised FOBT screening coverage in municipalities with a higher percentage of people with non-Belgian/Dutch nationality. The negative association between non-Belgian/Dutch nationality and organised CRC screening has also been shown in a previous Flemish study at the individual level [8]. Two main reasons for FOBT nonparticipation reported by migrants in Flanders are language issues and embarrassment when talking about CRC screening and stool samples [18].…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…Our study found a lower organised FOBT screening coverage in municipalities with a higher percentage of people with non-Belgian/Dutch nationality. The negative association between non-Belgian/Dutch nationality and organised CRC screening has also been shown in a previous Flemish study at the individual level [8]. Two main reasons for FOBT nonparticipation reported by migrants in Flanders are language issues and embarrassment when talking about CRC screening and stool samples [18].…”
Section: Discussionsupporting
confidence: 56%
“…Less time for sample collection at home has been reported as a reason for individuals not choosing FOBT as their preferred CRC screening method compared to (hypothetical) blood and saliva sampling [22]. A previous Flemish study at the individual level also found negative associations between organised FOBT screening with wage earners and being self-employed [8]. It was not possible to compare our findings regarding the association between employment and FOBT screening with other countries due to different systems of employment classification [15,16,20].…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Participation in FIT screening in Flanders is 52%, which explains why many CRCs are detected outside the screening programme. Non-participation could be due to symptoms, family history, socioeconomic status 25 or a recent CRC diagnosis (possibly fast growing). The CCD information flyer underscores that individuals with symptoms or CRC family history (increased risk for CRC) should seek advice from their general practitioner instead of participating in the FIT screening.…”
Section: Discussionmentioning
confidence: 99%